PERANAN KELUARGA DALAM MENANAMKAN SIKAP DISIPLIN ANAK PADA USIA REMAJA DI DESA TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sukinah, Sukinah; Hambali, Hambali; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the lack of discipline attitude of children at adolescent age in Teluk Mega Village, Tanah Putih Subdistrict, Rokan Hilir Regency. The lack of discipline included frequent night out, late leaving for school, smoking, denied parental orders to throw garbage carelessly and had not yet prayed five times. The formulation of the problem in this research is how the role of the family in instilling the attitude of child discipline in adolescence? This study aims to determine how the role of families in inculcating the attitude of child discipline in adolescence. The method in this research is descriptive qualitative. The subjects in this study were families who had children in the age of adolescents amounted to 337 Head of Family. The sample in this study amounted to 50 parents who have children in adolescence is between 10-19 years. Data collection techniques in this study are questionnaires, observation, interviews and documentation. From the results of the research, it is known that the role of the family in inculcating the attitude of children's discipline at the age of adolescents in Teluk Mega Village Tanah Putih Subdistrict Rokan Hilir Regency is good with the percentage of 72%. These results were obtained from the recapitulation of respondents' answers which answered very often by 27%, often by 44.9%, sometimes by 21.8% and never 6.3%. Based on the benchmark in CHAPTER III that is the number that answered very often+often that is 72% is in the range 50.01%-75.00% indicates good. The hypothesis formulation in this research is that the role of family in instilling discipline attitude of child at adolescent age is good. Thus the hypothesis in this study is accepted. From the results of this study is expected to be the material information or input for parents to always teach and instill to the child about good discipline.Key Words: Roles, Family, Youth Discipline